Problem

Are these steps for finding the solutions of  correct? (1)  is given; (2) x+3 = x2– 6x+9....

Are these steps for finding the solutions of  correct? (1)  is given; (2) x+3 = x2 6x+9. Obtained by squaring both sides of (1); (3) 0 =x27x + 6, obtained by subtracting x + 3 from both sides of (2): (4) 0 = (x - 1)(x 6). obtained by factoring the right-hand side of (3): (5) x = 1 or x = 6, which follows from (4) because ab= 0 implies that a = 0 or b = 0.

Step-by-Step Solution

Request Professional Solution

Request Solution!

We need at least 10 more requests to produce the solution.

0 / 10 have requested this problem solution

The more requests, the faster the answer.

Request! (Login Required)


All students who have requested the solution will be notified once they are available.
Add your Solution
Textbook Solutions and Answers Search
Solutions For Problems in Chapter 1.6